Nonlinear multi-mode electromagnetic insole energy harvester for human-powered body monitoring sensors: Design, modeling, and characterization. (November 2021) - Iqbal, Muhammad; Nauman, Malik Muhammad; Khan, Farid Ullah; Abas, Emeroylariffion; Cheok, Quentin; Aissa, Brahim
The current research in wearable electronics is trending towards miniaturization, portability, integration, and sustainability, with the harvesting of biomechanical energy seen as a promising route to improve the sustainability of these wearable electronics. Efforts have been made to prolong operational life of these harvesters, to overcome energy dissipation, lowering resonant frequency, attaining multi-resonant states as well as widening frequency bandwidth of these biomechanical energy harvesters. Herein, an electromagnetic insole energy harvester (EMIEH), capable of efficiently harvesting low-frequency biomechanical energy, has been designed, fabricated and experimentally tested. The core component in the device is the vibrating circular spiral spring, holding two magnets as the driving force on the central platform of the circular spiral spring, and just in-line with the upper and lower wound coils. It has been shown that the harvester exhibits higher sensitivity to low-frequency external vibrations than conventional cantilever-based designs, and hence allows low impact energy harvesting such as harvesting energy from walking, running and jogging. The experimentally-tested four resonant frequencies occurred at 8.9 Hz, 28 Hz, 50 Hz, and 51 Hz. At the first resonant frequency of 8.9 Hz under base acceleration of 0.6 g, the lower electromagnetic generator can deliver a peak power of 664.36 µW and an RMS voltage of 170 mV to a matching load resistance of 43.5 Ω. The upper electromagnetic generator can contribute an RMS voltage of 85 mV, corresponding to the peak power of 175 µW across 41 Ω under the same experimental condition. Finally, the harvester has been integrated into the shoe and it is able to charge a 100 µF capacitor up to 1 Volt for about 8 minutes foot movement. The result has remarkable significance in the development of wireless body monitoring sensors applications.